2014
DOI: 10.1126/science.1254009
|View full text |Cite
|
Sign up to set email alerts
|

Innate lymphoid cells regulate intestinal epithelial cell glycosylation

Abstract: Fucosylation of intestinal epithelial cells, catalyzed by fucosyltransferase 2 (Fut2), is a major glycosylation mechanism of host–microbiota symbiosis. Commensal bacteria induce epithelial fucosylation, and epithelial fucose is used as a dietary carbohydrate by many of these bacteria. However, the molecular and cellular mechanisms that regulate the induction of epithelial fucosylation are unknown. Here, we show that type 3 innate lymphoid cells (ILC3) induced intestinal epithelial Fut2 expression and fucosylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
420
2
9

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 465 publications
(463 citation statements)
references
References 56 publications
(116 reference statements)
15
420
2
9
Order By: Relevance
“…S7). It will be interesting to dissect the contributions of individual members of the microbiota such as segmented filamentous bacteria (18) and systemic signals acting through TLR (19) in TIR-dependent regulation of small intestinal fucosylation. Furthermore, we found that many UDP glucuronosyltransferases (Ugt) members show aberrant regulation in the colon in the absence of TIR signaling ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S7). It will be interesting to dissect the contributions of individual members of the microbiota such as segmented filamentous bacteria (18) and systemic signals acting through TLR (19) in TIR-dependent regulation of small intestinal fucosylation. Furthermore, we found that many UDP glucuronosyltransferases (Ugt) members show aberrant regulation in the colon in the absence of TIR signaling ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…IL-22 has been shown to play a critical role in mucosal immunity at barrier surfaces, including the gastrointestinal tract and in the lung (24). In the gut, IL-22 regulates the expression of antimicrobial proteins, such as Reg3␥ (25), and can also increase fucosylation through the upregulation of Fut2, resulting in enhanced resistance to pathogens (26)(27)(28). IL-22 can also activate STAT1 and increase antiviral immunity in the gut (23).…”
Section: Discussionmentioning
confidence: 99%
“…Further studies specifically depleting LTi‐like ILC3 are needed to determine whether these findings merely reflect redundancy among IL‐22‐producing ILC3 or subset‐specific roles in the regulation of commensal bacterial species. ILC3‐derived IL‐22 also results in fucosylation of intestinal epithelial cell‐associated carbohydrate chains following colonization of the intestinal tract by commensal bacteria 85, 86, 87. Whereas, certain species of mutualistic bacteria possess the necessary machinery to use carbohydrate fucose as an energy source, many pathogenic bacteria lack this ability and are outcompeted for energy sources.…”
Section: Ilc3 Functions Under Homeostatic Conditionsmentioning
confidence: 99%